Syntheses and evaluation of multicaulin and miltirone-like compounds as antituberculosis agents - GÖREN, AHMET CEYHAN; Burmaoglu, Serdar; Secinti, Hatice; MOZIOGLU, Erkan; Goren, AHMET CEYHAN; Altundas, Ramazan; SEÇEN, Hasan (My University, 2017)
Four multicaulin and miltirone-like phenanthrene derivatives were synthesised and evaluated as antituberculosis agents. The crucial step of the synthesis was Pschorr coupling of 4-(3-isopropyl-4-methoxyphenyl)-2-(2-aminophenyl)ethane (13) to give 2-isopropyl-3-methoxy-9, 10-dihydrophenanthrene (9) and 4-isopropyl-3-methoxy-9, 10-dihydrophenanthrene (9a). Compound 9 was converted to multicaulin and miltirone-like phenanthrene derivatives by further reactions. The best antituberculosis activity was exhibited by 2-isopropylphenanthrene-3-ol (11).